Making Farming Profitable to engage rural youth in agriculture - Gautam, Harender Raj (Indian Farming, 2015)
In India, 60 percent of our population depend on agriculture for their livelihood and agriculture contributes 14 percent in our Gross Domestic Product. Lower profits in agriculture are waning rural youth from agriculture and also driving the farmers to suicides in extreme cases. This is a serious challenge to our food security. There is urgent need to adopt new technologies and new crop production practices to increase productivity of major crops which is very low in comparison to other countries. Protected cultivation, food processing, agri-tourism and proper crop management to reduce the postharvest losses are some key areas which need attention and higher priority. Rural youth should be provided non-farm employment opportunities in the agro-processing industries or other industries based in the rural areas so that their income could be augmented to fulfil their aspirations.